(untitled) (American Journal of Islam and Society, 2022)
In the 1912 tome Unsere Zukunft: Ein Mahnwort an das deutsche Volk, Friedrich von Bernhardi once wrote: “war is the highest expression in life of a truly cultured people” (55). This book would argue for a more nuanced view of reality. In 1941 Nazi Germany and Fascist Italy invaded royal Yugoslavia and established a puppet regime called the ‘Independent State of Croatia’ (Nezavisna Država Hrvatska, or NDH). This polity included all of modern Bosnia-Hercegovina and included nearly one million indigenous Muslims. The dictatorship was led by an extremist Roman Catholic nationalist faction who initiated a campaign of brutal violence against citizens of the Serb Orthodox church and others, many of whom then turned their anger towards the mostly unarmed Muslim civilians. A cycle of religio-communal brutality erupted and several Islamic scholars and Muslim leaders signed a number of formal public resolutions: these documents resolutely condemned the bloodshed and carnage, and called on the authorities to enforce justice and peace, law and order. In retrospect, it was an act of remarkable courage and bravery.